(untitled) - Jarupongsakul, Somboon (Kyoto, 1990)
The purpose of discussing coastal development, mangrove shore can be grouped into two principal types based on the dominant mode of the coastal processes:(1) constructive mangrove shore, and (2) destructive mangrove shore,...
Keywords: Geology,Geomorphology,Địa chất học